The Cost Effectiveness in the Engineering Procurement and Construction (EPC) Contractors Industry in Indonesia, the Implementation, Obstacles and Application for Logistic Persons That Handled the Custom Matter - Widjanarko Widjanarko (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cost efficiency and cost effectiveness in a business is absolutely necessary. Accurate calculation of costs will determine competitive advantage. In the Contracting Services Industry sector, Engineering, Procurement and Construction (EPC) the joint use of several resources in carrying out projects is absolutely necessary to achieve company efficiency. A relatively appropriate method of calculating costs to overcome this is by applying the Activity Based Costing method. Application for the Logistic or Procurement Persons that handle the custom matter is a must.